Effective Solution for Scalability and Productivity Improvement in Fault-Tolerant Routing - Лемешко, О. В.; Tariki, N.; Kinan Arous (KHARKIV NATIONAL UNIVERSITY OF RADIO ELECTRONICS, 2015)
Effective solution for scalability and productivity improvement in fault-tolerant routing using the flow-based model was proposed. In practice, the fault- tolerant routing based on reservation of network resources is usually associated with decrease in overall performance and scalability of protocol solutions. In this regard, in structure of the model introduced conditions that are responsible for the fact that the primary and backup routes differed only by network elements for which redundancy provided. This was reflected in modification of objective function within the formulation and solution of optimization problem of the fault-tolerant routing. Numerical examples showed efficiency of the proposed solution
Keywords: TELECOMMUNICATIONS; flow-based model; fault-tolerance; routing; backup scheme; unicast